2018
DOI: 10.1186/s12978-018-0570-z
|View full text |Cite
|
Sign up to set email alerts
|

Women’s and communities’ views of targeted educational interventions to reduce unnecessary caesarean section: a qualitative evidence synthesis

Abstract: BackgroundThere is continued debate about the role of women and communities in influencing rising rates of caesarean section (CS). In settings where CS rates exceed recommended levels, mothers and babies are exposed to potential harms that may outweigh the potential benefits. There is therefore a need to understand how educational interventions targeted at women and communities to reduce unnecessary CS are perceived and used. This qualitative evidence synthesis aimed to explore what women and communities say a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 60 publications
1
77
0
1
Order By: Relevance
“…Pregnant women tend to identify health providers as the most important influence on their decision about mode of birth. 24,45,46 In contrast, health providers report women´s request as an important driver for performing non-medically indicated CS deliveries. A pan-European survey of 1530 obstetricians found compliance with a hypothetical women's request for CS without medical indications to be lowest in Spain (15%) and highest in the UK (79%).…”
Section: Factors Related To Health Professionalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant women tend to identify health providers as the most important influence on their decision about mode of birth. 24,45,46 In contrast, health providers report women´s request as an important driver for performing non-medically indicated CS deliveries. A pan-European survey of 1530 obstetricians found compliance with a hypothetical women's request for CS without medical indications to be lowest in Spain (15%) and highest in the UK (79%).…”
Section: Factors Related To Health Professionalsmentioning
confidence: 99%
“…65 Recent WHO recommendations on this topic (web appendix Table 1) drew on an updated Cochrane review (29 included studies), 12 and three qualitative evidence syntheses on women's and providers' views, values, beliefs and perceptions about CS, and factors related to organisations, facilities and systems (49 studies reported in 52 papers). 45,87,88 Below we present a summary of the findings of these reviews.…”
Section: Non-clinical Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussing the use of EBP might be an essential aspect to achieve a positive childbirth experience, contributing to change women's perception of fear of normal birth and believe that a cesarean is the safest type of birth. Women's voices and values need to be incorporated into a comprehensive childbirth model to reduce unnecessary C-sections (15,77).…”
Section: Creating Tailored Health Education Interventionsmentioning
confidence: 99%
“…Despite that the rate has declined to 47.9% in 2016, it remains high [15]. Given that the causes of the high CS rate are multifactorial, previous studies suggested that multifaceted interventions be used to decrease the CS rate [5,6,[16][17][18][19][20][21][22]. However, evidence concerning effective approaches to reduce unnecessary CS is limited [23,24], especially in China and other lowand mid-income countries.…”
Section: Introductionmentioning
confidence: 99%